Accumulation of TDP-43 causes karyopherin-α4 pathology that characterises amyotrophic lateral sclerosis - Atwal, Manpreet Singh; Nimac, Jerneja; Čerček, Urša; Goesch, Sarah Ricarda; Goesch, Hannah Rebecca; Tziortzouda, Paraskevi; Ercolani, Tiziana; Zatorska, Anna; Pasha, Terouz; Carre, Ivo; Mitchell, Jacqueline; Troakes, Claire; et al. (Frontiers in Neuroscience, 2025)
Cytoplasmic mislocalisation and nuclear depletion of TDP-43 are pathological hallmarks of amyotrophic lateral sclerosis (ALS), including mutations in the C9ORF72 gene that characterise the most common genetic form of ALS (C9ALS). Studies in human cells and animal models have associated cytoplasmic mislocalisation of TDP-43 with abnormalities in nuclear transport receptors, referred to as karyopherins, that mediate the nucleocytoplasmic shuttling of TDP-43. Yet the relationship between karyopherin abnormalities and TDP-43 pathology are unclear. Here we report karyopherin-α4 (KPNA4) pathology in the spinal cord of TDP-43-positive sporadic ALS and C9ALS patients. Structural analyses revealed the selective interaction between KPNA subtypes, especially KPNA4, with the nuclear localisation signal (NLS) of TDP-43. Targeted cytoplasmic mislocalisation and nuclear depletion of TDP-43 caused KPNA4 pathology in human cells. Similar phenotypes were observed in Drosophila whereby cytoplasmic accumulation of the TDP-43 homolog, TBPH, caused the nuclear decrease and cytosolic mislocalisation of the KPNA4 homolog, Importin-α3 (Impα3). In contrast, induced accumulation of Impα3 was not sufficient to cause TBPH mislocalisation. Instead, targeted gain of Impα3 in the presence of accumulating cytosolic TBPH, restored Impα3 localisation and partially rescued nuclear TBPH. These results demonstrate that cytoplasmic accumulation of TDP-43 causes karyopherin pathology that characterises ALS spinal cord. Together with earlier reports, our findings establish KPNA4 abnormalities as a molecular signature of TDP-43 proteinopathies and identify it as a potential therapeutic target to sustain nuclear TDP-43 essential for cellular homeostasis affected in ALS and frontotemporal dementia.